Role of B cells in antigen presentation of the hepatitis B core - Milich, David R. (The National Academy of Sciences of the USA, 1997)
The hepatitis B virus (HBV) nucleocapsid or core antigen (HBcAg) is extremely immunogenic during infection and after immunization. For example, during many chronic infections, HBcAg is the only antigen capable of eliciting an immune response, and nanogram amounts of HBcAg elicit antibody production in mice. Recent structural analysis has revealed a number of characteristics that may help explain this potent immunogenicity. Our analysis of how the HBcAg is presented to the immune system revealed that the HBcAg binds to specific membrane Ig (mIg) antigen receptors on a high frequency of resting, murine B cells sufficiently to induce B7.1 and B7.2 costimulatory molecules. This enables HBcAg-specific B cells from unprimed mice to take up, process, and present HBcAg to naive Th cells in vivo and to T cell hybridomas in vitro approximately 10(5) times more efficiently than classical macrophage or dendritic antigen-presenting cells (APC). These results reveal a structure–function relation for the HBcAg, confirm that B cells can function as primary APC, explain the enhanced immunogenicity of HBcAg, and may have relevance for the induction and/or maintenance of chronic HBV infection.